Nghiên cứu sử dụng vi sinh vật để chế biến bã thải rong câu làm thức ăn chăn nuôi - Huy, Đỗ Quang; Phượng, Trịnh Thị; Dương, Ngô Thị Thùy; Chi, Đỗ Thị Quỳnh (VNU Journal of Science: Natural Sciences and Technology, 2006)
Abstract